Manajemen pengelolaan limbah medis di praktik dokter gigi Kabupaten Tabanan - Dewa Ayu Putu Gek Mega Suryasih Putri; Ni Kadek Fiora Rena Pertiwi; Ni Made Sri Nopiyani (School of Dentistry Faculty of Medicine Udayana University, 2018)
Health care activity in dental practice produce dental waste, that can cause problem if it is not treated properly. The prevalence of Tabanan citizen who receive dental treatment is the second highest after Denpasar which is 48,3%. The purposes of this study are to understand the dental waste management, reinforcing factor and obstacle in dental waste management. This study is a qualitative study. The samples were obtained from 6 dental practices providing BPJS and 6 dental practices non providing BPJS in rural and urban area, located in Tabanan Regency, selected using purposive sampling. Data collection methods were observation and in-depth interview. Data analysis using thematic analysis. The result of this study showed that dental and non dental waste were segregated but, some waste containers were inappropriate. For example using mineral water bottle as a sharp waste container, using thin plasctic bag and there is no labelling on waste container. Waste packaging was done by tying the plastic bag in a usual way. There is no specific place for storing the dental waste. Dental waste were transported by dentist using their vehicles. The waste burnt down in community health center and hospital’s incinerator, but there are 2 informants who burnt it down in an empty lot near their office. Public Health Office give policy regarding dental waste management but there are no standard operating procedure and no periodic monitoring. Dental waste management in dental practice Tabanan does not fully meet the requirement. It is necessary to create a clear standard operating procedure, periodic monitoring and technical guidance for the dentist.